Aplikasi Game Life Simulation Peternakan Domba Menggunakan Metode Fuzzy - Evelyn Njoto; Liliana Liliana; Rolly Intan (Jurnal Infra, 2016)
Many people are eager to learn more about the world of farming, not just knowing the name and shape of the animal. However, not everyone can travel to the farm to learn about the life cycle of the animal. One way that can be used to provide a learning experience about the life cycle of living beings in the fastest way is through a game. One of the game’s genres that can be used to provide entertainment and educational aspects to the players is a life simulation. As a life simulation game, the data used is from the real studies of sheep. To give a more realistic situation, this game has a fuzzy state machine to determine the behavior shown by the animals when being approached by the opposite sex.By creating the simulation of sheep with three-dimensional interface, the player will enjoy the gaming experience more similar to the real world. This will give more pleasure to the player. This game was made using the Unity Engine and scripting using C # with MonoDevelop. From the test results, the majority of sheep AI performance is partly influenced by changes in the inputs necessary for the calculation of fuzzy and largely influenced by the interaction of the player in the game.